2018
DOI: 10.1590/s1980-6574201800010004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring training load in beach volleyball players: a case study with an Olympic team

Abstract: Aim: Describe and compare training load dynamics of two Olympic beach volleyball players. Methods: Two Olympic beach volleyball players participated in this study (specialist defender and blocker: both aged 34 years, holding 14 years of competitive experience, height: 1.74 m and 1.81 m, weight: 69 kg and 65 kg, respectively). Internal training load (ITL), total weekly training load (TWTL), monotony and strain were obtained through the session rating of perceived exertion (session-RPE) for three training mesocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…In beach volleyball players, the monitoring data from wearable sensors has been used to model the injury risk via artificial neural network [68]. These studies highlight the importance of adequate management of training load in these sports too [99–101] along with the use of technology and innovative approaches in data management in order to protect the athletes’ health [102, 103].…”
Section: Discussionmentioning
confidence: 99%
“…In beach volleyball players, the monitoring data from wearable sensors has been used to model the injury risk via artificial neural network [68]. These studies highlight the importance of adequate management of training load in these sports too [99–101] along with the use of technology and innovative approaches in data management in order to protect the athletes’ health [102, 103].…”
Section: Discussionmentioning
confidence: 99%
“…Works analyzing ITL in beach volleyball 7,15 with the use of s-RPE refer to an imbalance between loading and recovery to evolve non-functional overreaching and overtraining. 7 These authors moreover suggest sudden changes in training load (Acute-Chronic ratio) as risk factor but omit marker or load specifications for training monitoring. In this investigation, the number of total actions and total time under action was similar between the different session types.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The reduced number of players and larger area to cover increase the individual stress level during training and competition compared to regular volleyball settings. 10,7 In order to monitor internal training response, different markers (session rate of perceived exertion [s-RPE], Delayed onset of muscle soreness [DOMS] and creatinkinase [CK]) were analyzed for indoor volleyball 8,11,12 but only one work evaluated elite beach volleyball players. 7 The authors identified different levels of s-RPE among blockers and defenders and between different mesocycles within a 10 week observation in a case study of 2 elite players.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations